Modern Treatment of Diseases of the Oral Mucosa and Periodontal Under the Influence of Covid 19 - Giyazova M. M. (Researchparks Publishing, 2021)
Relevance. Diseases of the oral mucosa can manifest themselves by various nosological processes of the oral cavity, but sometimes even against the background of pronounced inflammatory processes, stomatitis, gingivitis and many other diseases do not form, often this is due to systemic viral processes, for example, coronavirus infection [12.14.15]. At the same time, clinical symptoms can be very diverse, or even absent even against the background of changes in the immune and microbial landscape of the oral cavity. With the progression of the disease, the spread of the process to the palate, gums, palatine tonsils, larynx, digestive tract may be noted. It is important to isolate weakened individuals, individuals with immunodeficiency conditions who have been on long-term use of antibacterial agents, corticosteroids and antineoplastic drugs [1.3.4.7.9]. The persistence and recurrent nature of such inflammatory lesions requires not only the usual hygienic measures for the care of the oral cavity and teeth, but also appropriate justified therapy aimed at stimulating the protective forces of the oral mucosa. The oral cavity is anatomically and functionally connected with the pharynx, inflammatory diseases of which are currently in the focus of attention of otolaryngologists due to their wide prevalence, and mainly in people of working age. These diseases are dangerous because they can cause the development of severe complications from the cardiovascular system, kidneys and joints [12.14.15.16].